Pemberdayaan Sosial dan Ekonomi Kreatif dalam Upaya Meningkatkan Kesejahteraan Masyarakat Pesisir Desa Mantang Lama - Pepriyana, Adiya; Anggrainy, Novita; Sahadatul Alawiyah, Nur; Wahyuni, Sri (STISIPOL Raja Haji, 2024)
This article was written to describe that the Coastal Village Community in Bintan Regency, namely the Old Mantang Village, where the majority of the people work as fishermen, still depend on entrepreneurs or toke, so these results cannot meet their daily living needs. So the fishermen's wives took the initiative to sell to help their family's economy. Therefore, the village government is making efforts to improve and develop the economy with the aim of improving the welfare of the people of Mantang Lama Village. The aim of this research is to find out and understand how community empowerment is carried out by the Mantang Lama Village government in an effort to improve the economy and also the welfare of the coastal communities of Mantang Lama Village. The method used in this research is a qualitative research method with descriptive explanations. The data source in this research uses primary and secondary data sources. The results of this research are that the village government through BUMDes Mantang Lama formed KUBE Mawar Merah with the aim of empowering the community so that their economy can increase and be able to improve the social welfare of the people of Mantang Lama Village.